Pengaruh Model Pembelajaran Word Square Berbasis Tri Kaya Parisudha Terhadap Hasil Belajar IPA - Cahyana, Gd. Roni; Sudana, Dewa Nyoman (Universitas Pendidikan Ganesha, 2019)
This study aimed at investigating whether or not there was a significant effect on science learning achievement of students who were taught by using Word Square learning model based on Tri Kaya Parisudha and who were not taught by using Word Square learning model based on Tri Kaya Parisudha in the fifth grade students at SDN Gugus 6 Sutasoma Kubutambahan Sub-District in accademic year 2017/2018. This study was a quasi-experimental research. The population of this study was the 141 students of fifth grade students at SDN Gugus 6 Sutasoma Kubutambahan Sub-district. The research sample were 14 students of the fifth grade students at SD Negeri 5 Tajun and 16 students of the fifth grade students in SD Negeri 6 Tajun. The data were collected by using test method, the instrument was science learning achievement test and used in the form of multiple choice test. The obtained data were analyzed by using descriptive statistical analysis techniques and inferential statistical analysis which was t-test. The average value of the two classes, namely the experimental group was 23.64 while the control group was 16.25. The result of data analysis showed that thitung = 5.28> ttable = 2.048. Based on the results of this study, it can be concluded that there was an effect of Word Square-learning model based on Tri Kaya Parisudha on students’ science learning achievement of the fifth grade students at SDN Gugus 6 Sutasoma Kubutambahan Sub-district in academic year 2017/2018.